Matching phylogenetic relationship with advertisement call characteristics of the male bornean hylarana baramica - Cheok, Melynda Ka Yi (Universiti Malaysia Sarawak (UNIMAS), 2012)
The study is done with samples from four different locations, which are the east campus of Universiti Malaysia Sarawak (UNIMAS), Matang Wildlife Centre, Bako National Park, and Mulu National Park. The advertisement calls of male anurans are different between species as it is a motivation for them to reproduce their next generation, and also in ensuring the survivorship of the particular species by maintaining reproductive isolation among population. In this study, the phylogenetic relationship of different Hylarana baramica population were determine by using partial mitochondrial DNA COI gene. DNA extraction protocol was used for the extraction of DNA obtained from the muscle tissue samples. Whereas annealing temperature in PCR amplification of the species is 50°C. The phylogenetic relationship was analysed using Phylogenetic Analysis Using Parsimony (PAUP) version 4.0. As for the analysis of advertisement call characteristics, SoundRuler Acoustic Analysis version 0.9.6.0. was used to analyse 38 characters from the recorded call for all of the individuals. While, MultiVariate Statistical Package (MVSP) version 3.1 was used to generate cluster analysis of the call characteristics. The call characteristic analysis showed no specific clustering group of each population. However, the phylogenetic data are insufficient to match the phylogenetic relationship with advertisement call characteristics of the different population of Hylarana baramica.